2021
DOI: 10.2166/wst.2021.361
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the adsorption of methylene blue by particulate durian peel waste in water

Abstract: This study aims to investigate the adsorption of methylene blue (MB) over particulate durian peel waste, which is chemically-activated with hydrogen peroxide. The equilibrium data is well-described by the Freundlich isotherm model, which outlines where the MB adsorption takes place predominantly on multilayers and heterogeneous surfaces of the biosorbent. The Freundlich adsorption constants, KF and n, are 11.06 L/g and 2.94, respectively. Thermodynamic data suggests that the MB adsorption occurs spontaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…It has been reported that, depending on the composition of the botanical extract used, a high affinity between the functional groups of the extracts and dye molecules can occur [ 44 ]. Further, surfaces modified with functional groups have been tested and it has been demonstrated how the interaction with methylene blue is improved, and therefore, the adsorption is increased [ 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that, depending on the composition of the botanical extract used, a high affinity between the functional groups of the extracts and dye molecules can occur [ 44 ]. Further, surfaces modified with functional groups have been tested and it has been demonstrated how the interaction with methylene blue is improved, and therefore, the adsorption is increased [ 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…dye molecules can occur [44]. Further, surfaces modified with functional groups have been tested and it has been demonstrated how the interaction with methylene blue is improved, and therefore, the adsorption is increased [45][46][47][48].…”
Section: Recyclability Of Zno Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The precursor used for activated carbon production is plant biomass activated carbon (activated carbon lignocellulose) which is a complex carbohydrate polymer with main components including cellulose, lignin, and hemicellulose. Lignocellulosic activated carbon can be found in agricultural and industrial waste such as duckweed [ 2 ], potato stalks and leaves [ 3 ], bamboo plants [ 4 ], mango leaves [ 5 ], tea residues [ 6 , 7 , 8 ], rice husk [ 9 , 10 ], sawdust [ 11 ], durian seeds and peel [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ], neem leaves [ 19 ], moringa leaves and seeds [ 20 , 21 ], mangosteen peel [ 22 , 23 , 24 , 25 ], chitosan [ 26 ], pear fruit seeds [ 27 ] and acorn shells [ 28 ]. The activated carbon made from agricultural food waste has high economic efficiency in wastewater treatment due to abundant raw materials and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…The shell is a residue that accounted for 70–85% of the durian fruit weight. In durian shells, there are three basic components: cellulose (30.92%); hemicellulose (17.99%) and lignin (7.69%) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Therefore, the durian shell is a precursor for manufacturing and investigating the adsorption of metal ions [ 14 ] and dyes [ 12 , 14 , 15 , 18 ] in an aquatic environment.…”
Section: Introductionmentioning
confidence: 99%